How prominent science communicators on YouTube understand the impact of their work - Hill, Vanessa M.; Grant, Will J.; McMahon, Melanie L.; Singhal, Isha (Frontiers in Communication, 2022)
YouTube is rapidly becoming one of the major places that people around the world engage with science, in turn making prominent science communicators on YouTube some of the most impactful and known faces in science communication. However, while much is known about the viewership habits of YouTube audiences, little is known about the motivations, thinking and ideas of impact of the science communicators working on YouTube. The current study qualitatively explored these questions via one-on-one interviews with prominent science communicators working on YouTube (n = 20). We explore their responses in six key areas: their understanding of and relationship with their audience; their attitude toward impact metrics; their attitude toward comments; their understanding of impact; their reasons for creating content; and what it is like working under the algorithm. Key findings include a wide variety of opinions about the metrics provided by YouTube; a near unanimous assertion of the value of comments; a somewhat deficit model approach to their communication work; and a polarised attitude to working under the algorithm.